(untitled) (Medical Forum Monthly, 2020)
Objective: To compare the effectiveness of oral versus topical metronidazole for reducing postoperative pain in patients undergoing Milligan Morgan hemorrhoidectomy. Study Design: Randomized controlled trial study. Place and Duration of Study: This study was conducted at the Department of Surgery, Divisional Headquarter Teaching Hospital Mirpur AJK from July 2019 to June 2020. Materials and Methods: One hundred and twenty patients of both genders with ages 20 to 60 years undergoing hemorrhoidectomy for 3rd and 4th degree hemorrhoids were enrolled. All the patients were equally divided into two groups, each group contains 60 patients. Group 1 received oral metronidazole postoperatively for 5-days and group 2 received topical metronidazole postoperatively. Postoperative pain was analyzed by VAS on 1st, 3rd and 5th day postoperatively between both groups. Results: There were 76 (63.33%) male patients and 44 (36.67%) were females with mean age 38.74±11.42 years. 67 (55.83%) patients had 4th degree hemorrhoidal disease and 53 (44.16%) patients had 3rd degree disease. Group 2(topical) patients had significantly lower postoperative pain at 5th day as compared to group 1(oral) patients with p value<0.05. Conclusion: Topical metronidazole is more effective than oral metronidazole in patients undergoing Milligan Morgan hemorrhoidectomy.